ANALISIS MODEL PENGEMBANGAN PULAU OSI DI KABUPATEN SERAM BAGIAN BARAT SEBAGAI KAWASAN WISATA BAHARI BERKELANJUTAN - Patmawaty Hehanussa; Muhammad Kasnir; Danial Danial (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
This study aims (1) to analyze the relationship between external and internal factors on the sustainability of the marine tourism of Osi Island and (2) formulate a model for the development of marine tourism in Osi Island. This type of research is quantitative descriptive research. Data sources are tourists who are and have been to Osi Island. Techniques used in data collection include field studies / observations and literature studies. Data analysis was performed using a strucktural equation model (SEM) analysis with AMOS analysis tools. The results showed that: (1) Variable internal and external factors significantly influence the sustainability of tourism on Osi Island where human resources are more dominant to contribute to this due to community awareness in the local village in terms of maintaining cleanliness and managing existing nature. Based on this it can be said that in terms of environmental aspects the marine tourism area of Osi Island has fulfilled what is said to be sustainable. (2) the final model of this research is interpreted for the future development plan of Osi Island where the development plan must be based on the vision of sustainable tourism and because Osi Island is a self-managed tourism area, it can develop a community-based tourism model with all stakeholders related namely the central government, local government, etc. can participate in the development both directly and indirectly so that the impact of the development of the model results in an independent community from all aspects.